Psychological peculiarities of language use among Ukrainian migrants in Poland speaking Ukrainian and Russian languages: Психологічні особливості використання мови україномовними та російськомовними українськими мігрантами в Польщі - Danyliuk, Ivan; Shykovets, Sergiy (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2019)
The article presentsresults of the study and practical analysis of the phenomenon of the influence of ethnolinguistic identity on the formation of the language image, as well as the psychological well-being and personal health of Ukrainian-speaking and Russian- speaking Ukrainian migrants in Poland. The article attempts to reveal the value of the welcoming status of linguistic identity as a means to achieve the psychological well-being of a personality in a modern multicultural society. The prospects for studying the impact of ethnolinguistic identity and psychological well-being and the personal health of representatives of Ukrainian language communities and migrant groups with prediction of possible spheres of application of the obtained results are also described.